Exergoeconomic optimization and experimental investigation of a solar heating system with thermal energy storage in Turkey - Ucar, Aynur; Oral, Abdurrahman (Taylor & Francis Inc, 2021)
Thermal energy storage is a promising environmentally friendly technology to improve the efficiency of renewable energy sources. In this study, the solar energy was stored using the water in the bottles emplaced in the heat store for heating a security cabinet. The thermal performance of a daily solar energy storage system for heating a security cabinet is investigated. The energy and exergy losses in each of the components of a daily solar energy storage system were also determined. The daily mean rate of the heat kept inside the heat store was 2.15 kW and thermal exergy rate was 386 W for this charge period. The daily mean energy efficiency and exergy efficiency were obtained as 83% and 55.3%, respectively. The daily mean heat rescued from the heat store was defined as 2.25 kW and thermal exergy was 725 W for the discharge period. An exergoeconomic model was developed for optimum sizes of the collector and storage in a solar heating system, and these results were compared with the experimental study. When the design values and optimum values were compared in experimental studies, an increase of 48.6% in exergetic efficiency and a decrease of 49.3% in total exergy cost were obtained.
Keywords: Building heating; energy and exergy analyses; heat storage; solar energy